Functional response of the predatory mite Chileseius camposi (Acarina: Phytoseiidae) on densities of it prey, Panonychus ulmi (Acarina: Tetranychidae) - Sepúlveda, Francisco; Carrillo, Roberto (Revista de Biología Tropical, 2008)
The functional response of the phytoseiid predator Chileseius camposi González y Schuster, 1962 (Acarina:Phytoseiidae) on densities of its prey Panonychus ulmi (Koch, 1836) was evaluated under controlled temperature (20 ± 2 C), relative humidity (75 ± 15%) and photoperiod (16:8h L:D). A functional type II response was displayed (Holling's disk). Holling, Wolf transformation and Rogers models gave similar values for estimating parameters of the Holling's disk equation; however, estimates produced by the Livdahl and Stiven model were higher. Values of attack rate and handling time can be considered within the normal range for phytoseiid generalists.